Chromosomal-Level Genome Assembly of the Sea Urchin Lytechinus variegatus Substantially Improves Functional Genomic Analyses. (20th May 2020) - Davidson, Phillip L; Guo, Haobing; Wang, Lingyu; Berrio, Alejandro; Zhang, He; Chang, Yue; Soborowski, Andrew L; McClay, David R; Fan, Guangyi; Wray, Gregory A
Abstract: Lytechinus variegatus is a camarodont sea urchin found widely throughout the western Atlantic Ocean in a variety of shallow-water marine habitats. Its distribution, abundance, and amenability to developmental perturbation make it a popular model for ecologists and developmental biologists. Here, we present a chromosomal-level genome assembly of L. variegatus generated from a combination of PacBio long reads, 10× Genomics sequencing, and HiC chromatin interaction sequencing. We show L. variegatus has 19 chromosomes with an assembly size of 870.4 Mb. The contiguity and completeness of this assembly are reflected by a scaffold length N50 of 45.5 Mb and BUSCO completeness score of 95.5%. Ab initio and transcript-informed gene modeling and annotation identified 27, 232 genes with an average gene length of 12.6 kb, comprising an estimated 39.5% of the genome. Repetitive regions, on the other hand, make up 45.4% of the genome. Physical mapping of well-studied developmental genes onto each chromosome reveals nonrandom spatial distribution of distinct genes and gene families, which provides insight into how certain gene families may have evolved and are transcriptionally regulated in this species. Lastly, aligning RNA-seq and ATAC-seq data onto this assembly demonstrates the value of highly contiguous, complete genome assemblies for functional genomics analyses that is unattainable with fragmented, incomplete assemblies. This genome will be of great value to the scientific community as a resource for genome evolution, developmental, and ecological studies of this species and the Echinodermata.